(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Data United International Children’s Emergency Fund (UNICEF) 2020 stated that growth and development disorders in children under five were 27.5%. From the results of a preliminary study on Friday 19 May 2023, TK ABA Pasekan Sleman had 74 students, 37 boys and 37 girls. There are 5 students who experience motor disorders, one of whom is not fluent in reading, writing and drawing, the majority of whom are 6 years old and want to enter elementary school. Meanwhile, around 50% of children still have problems reading and writing. Result of survey The teacher’s introduction at the ABA Pasekan Kindergarten stated that mothers did not know how to stimulate children according to their age. One mother even only followed her child’s wishes so that the child rarely went to school. According to an interview with ABA Pasekan Kindergarten Teachers, Early Growth and Development Intervention Detection Stimulation (SDIDTK) was carried out from the Community Health Center, but this year it has not been carried out. Purpose: Knowing the description of mothers’ level of knowledge regarding the meaning, forms and principles of growth and development stimulation for preschool children at the ABA Pasekan Kindergarten. Method: The research design used is a quantitative descriptive research design with a quantitative approachcross sectional. The samples taken were 74 mothers usingtotal sampling. The research was conducted in May-June 2023. Result: It shows that some respondents, namely 51 mothers (68.9%) have good knowledge. Meanwhile, 23 mothers (31.1%) had insufficient knowledge. The results of the research stated that some respondents had good knowledge due to the characteristics of the respondents, most of whom had a high school/vocational high school-university education of 62 (83.8%). Keywords: Growth and development, motor skills, knowledge